Enhancing Students' Logical Thinking through Ethnomathematics-based Augmented Reality of Bola Soba Character Facades - Sartika Sari Dewi; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Andi Nurannisa; Wiwi Damayanti; Nining Wahyuni (Yayasan Keluarga Guru Mandiri, 2024)
Logical thinking skills are crucial for students to navigate increasingly complex learning processes, as these skills are part of Higher-Order Thinking Skills (HOTS). They involve analyzing problems scientifically and systematically to make informed generalizations. Unfortunately, national and international surveys show that students' logical thinking skills remain low. This study investigates how implementing ethnomathematics-based Augmented Reality through the façade of the Bola Soba character building can enhance students' logical thinking skills. A quasi-experimental research method with a non-equivalent control group design was applied at one public school in South Sulawesi, focusing on eighth-grade students. Two classes were sampled using purposive nonprobability sampling: 30 students in class VIII B as the experimental group and 30 in class VIII A as the control group. Results revealed a significant improvement in the experimental group, with a gain score of 0.70 (70%), categorized as high. This indicates that using ethnomathematics-based Augmented Reality significantly enhances students' logical thinking skills. The study contributes to the field by showing how local wisdom, represented by Bola Soba facades integrated with modern educational technology, can foster students' cognitive development.